Dimensions of Online Behavior: Implications for Engineering E-Learning - Johnson, Genevieve; Johnson, J. (Springer, 2010)
E-learning occurs as a function of instructional applications of Internet technologies in conjunction with a range of student intellectual and personal characteristics. E-students vary in terms of their patterns of online behavior, defined as organized (e.g., web search) and disorganized (e.g., browse) interactions with both human (e.g., chat) and nonhuman (e.g., database) elements in online environments. Online behavior is conceptualized in terms of the dimensions of sociability (human connection motives), utility (efficiency orientation), and reciprocity (the need for cognitive stimulation and active involvement when using the Internet). Eight individuals from various disciplines completed the Brief Test of Online Behavior and received scores on the three dimensions of online behavior. Although variation was apparent, the professional engineer was not distinguished by his scores on sociability, utility, or reciprocity, suggesting that all three dimensions of student online behavior should be considered in e-learning pedagogy.